Creative Learning Strategies at SD Muhammadiyah Labschool during the Covid-19 Pandemic - Firyalita Sarah Firdaus; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study discusses creative learning strategies at SD Muhammadiyah 1 Candi Labschool UMSIDA which have changed, namely by using an online or online system. This study aims to determine the creative strategies used by Muhammadiyah elementary school teachers in the midst of the Covid-19 pandemic situation. The method used by the author is a descriptive qualitative research method to explore information related to the issues raised. The results of this study indicate that SD Muhammadiyah 1 Candi Labschool UMSIDA developed a new learning strategy as a solution in dealing with the covid-19 pandemic, namely by conducting online learning using the Zoom application, Google Meet, Microsoft Team, WhatsApp. While the teacher's own creative strategy uses a personalized method strategy, which uses a discussion system and play while learning strategies, so students play while learning so that students can be motivated in learning. So teaching and learning activities at SD Muhammadiyah 1 Candi Labschool UMSIDA can run well.